Echoes from "Fight Club": Categorical Thinking, Narrative Strategies, and Political Radicalism in Chuck Palahniuk’s "Adjustment Day" - Collado Rodríguez, Francisco (Journal of English Studies, 2022)
This work addresses Chuck Palahniuk’s novel Adjustment Day as a satirical critique of the political radicalization of the USA and as a warning about the dangerous ideological effects narratives may have on our posthumanist understanding of reality. To reach his purposes, the novelist combines three stylistic strategies. First, he creates a satirical story that exposes the condition of American politics, the dangers of radicalized political correctness, and the present risks of populist revolutions. Secondly, he uses explicit metafictional references to Fight Club and to other literary works and critical theories to warn about the dangerous effects that the power of narrative can have. Finally, Palahniuk departs from the minimalist style he used in his earlier and most well-known fiction in favor of a heterodiegetic and omniscience narrative voice that, combined with multiple internal focalizations, endorses a plural, non-categorical understanding of reality.